Overview of Heart Disease Patients' Lifestyle in Sidikalang Regional General Hospital, Dairi District in 2024 - Silalahi, Roberth Harnat; Pandiangan, Irawati; Silaban, Jojor (International Journal of Public Health Excellence (IJPHE), 2024)
Background: Heart disease is not only a threat of pain but also a disease that lurks with the threat of death. This disease can cause a high death rate. According to WHO 2018, around 31% of all deaths in the world, and the majority or around 8.7 million, are caused by heart disease. According to Riskesdas 2018, the prevalence in Indonesia reached 1.5%. Heart disease can be triggered by various lifestyle factors, including a lifestyle with smoking habits, consuming alcohol, exercise habits, the habit of consuming pickled and preserved foods, and a history of obesity. Objective Objective: find out the description of the lifestyle of heart disease sufferers at the Sidikalang Regional General Hospital, Dairi District in 2024. Method: This type of research was descriptive, and carried out from January to April 2024. The population in this study is 235 people with heart disease, using an accidental sampling technique, the total sample was 70 people. Results: Lifestyle after suffering from heart disease, the majority did not smoke as much as 61.42% and were heavy smokers as much as 10%, the majority did not have the habit of consuming alcohol as much as 68.51% and had the habit of consuming alcohol frequently alcohol 12.85%, the majority do exercise enough as much as 22.4% and do not exercise 14.7%, the majority sometimes consume pickled and preserved foods as much as 37.14%, and those who do not consume salted and preserved foods as much as 21.42% , the majority were not obese as much as 37.1% and obesity was 11.9%. Better health services are expected to provide education about the lifestyle of heart disease sufferers.